2014
DOI: 10.1002/jmor.20335
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of antennal sensilla of the peach aphid Myzus persicae Sulzer, 1776

Abstract: The antennal sensilla of alate Myzus persicae were mapped using transmission electron microscopy and the ultrastructure of sensilla trichoidea, coeloconica, and placoidea are described. Trichoid sensilla, located on the tip of the antennae, are innervated by 2-4 neurons, with some outer dendrites reaching the distal end of the hair. Coeloconic sensilla in primary rhinaria are of two morphological types, both equipped with two dendrites. Dendrites of Type II coeloconic sensilla are enveloped in the dendrite she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
4
6
0
Order By: Relevance
“…Coeloconic sensilla have been reported that they are involved in thermo-/hygroreceptive functions in both Lepidoptera and Diptera (Sutcliffe, 1994). Similar to what was described in other aphid species (Bromley et al, 1980), two types of trichoid sensilla have been reported in our study, which could be involved in mechanosensing and/or in contact chemoreception (Bromley et al, 1980;Sun et al, 2013;Ban et al, 2015). Type II trichoid sensilla localized on the antennal tip and crowned by five blunt tipped uniporous hair, implying a gustatory function for these sensilla (De Biasio et al, 2015).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Coeloconic sensilla have been reported that they are involved in thermo-/hygroreceptive functions in both Lepidoptera and Diptera (Sutcliffe, 1994). Similar to what was described in other aphid species (Bromley et al, 1980), two types of trichoid sensilla have been reported in our study, which could be involved in mechanosensing and/or in contact chemoreception (Bromley et al, 1980;Sun et al, 2013;Ban et al, 2015). Type II trichoid sensilla localized on the antennal tip and crowned by five blunt tipped uniporous hair, implying a gustatory function for these sensilla (De Biasio et al, 2015).…”
Section: Discussionsupporting
confidence: 89%
“…As previously described, we also observed the presence of multiple pores on the surface of the outer cuticle of placoid sensilla (Bromley et al, 1979), indicating they are typical olfactory chemoreceptors (Steinbrecht, 1984). We found that the number of secondary rhinaria (placoid sensilla) on the antenna are very similar between alate and apterous T. trifolii (Table 1), while secondary rhinaria were seldom found in apterous morphs of other aphids such as M. persicae and A. pisum (Table 1; Shambaugh et al, 1978;Sun et al, 2013;Ban et al, 2015;De Biasio et al, 2015). In addition, the ultrastructure of secondary rhinaria (placoid sensilla) is also very similar between alate and apterous morphs in T. trifolii, and further studies need to confirm this phenomenon in other aphids.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Many sensilla are present on the antennae, and their number and type vary amongst different species. The sensory plaque organ is a common type of sensillum in hemipteran insects, including Delphacidae, Aphididae and Fulgoridae (Bourgoin and Deiss, ; Shih and Yang, ; Liang, ; Park and Hardie, ; Ban et al , ). Previous studies have not focused on the genes that regulate development of the sensory plaque organ.…”
Section: Discussionmentioning
confidence: 99%